বাংলা ও বাঙালির কথা - মোমেন, আবুল; Ahmed, A. F. Salahuddin, 1924-2014 (ঢাকা : সাহিত্য প্রকাশ, 2010)
Articles chiefly on the history of Bengali, South Asian people and Bengal.
Includes bibliographical references (page 122).
In Bengali.
Keywords: Bengali (South Asian people) -- History; Bengal (India) -- History